Aboriginal health policy: is nutrition the 'gap' in 'Closing the Gap'? - Jennifer Browne; Rick Hayes; Deborah Gleeson (Elsevier, 2014)
Abstract Objective: To examine the extent to which nutrition has been prioritised in national Aboriginal and Torres Strait Islander health policy. Method: Australian Government websites were searched for Aboriginal‐specific health policies and strategies developed between 2000 and 2012. Thirteen documents describing nine policies were analysed. Results: Increased and more comprehensive inclusion of nutrition in Aboriginal health policy was identified during the first half of this period. In the second half, however, nutrition strategies were fragmented, and a much greater emphasis was placed on smoking. Conclusion and Implication: With the exception of food security in remote communities, nutrition seems to have disappeared from the national Aboriginal health policy agenda. This is a concern, given the burden of nutrition‐related disease in the Aboriginal and Torres Strait Islander population.